Biosurfactant Enhanced Bioelectrokinetic Remediation of Petrochemical Contaminated Soil - Chirwa, Evans M.N. (University of Pretoria, 2021)
Dissertation (MEng (Environmental Engineering))--University of Pretoria, 2019.